فهرسة المخطوطات العربية ماهيتها، أنواعها، واقعها ومدى نجاعتها - بورمل, حسين (Revues faculté des lettres et des langues; Vol. 1 No 21 (2017): مجلة كلية الآداب و اللغات, 2018)
Abstract: Possibly the manuscripts were not effortless at the beginning of their emergence in terms of selecting the manuscript and finding a copy, also to see the investigator she offers more than others, did not argue the matter to what has become necessary later, the knowledge of the investigator and mave on the Arab bibliographic for consideration that had been achieved and what is determined to be achieved or not. With the enormous popularity of achieving Arab heritage, there was an urgent need there emerged to create specialized centers in the preservation of manuscripts and indexation. Then the Arab library became full of books and manuscripts. These indexes were not without benefits and facilities for researchers, but it has always been a deficient knowledge of all the elements of cataloging manuscripts due to the nature of the paper, and the lack of possibility foram easy modification, manipulation, refresh and renewal. الملخص لعل تحقيق المخطوطات كان أمرا هينا في بداية ظهوره من ناحية انتقاء المخطوط وإيجاد نسخه، ولمعرفة المحقق أنه يُقْدم على ما لم يقترب منه غيره، فلم يحتج الأمر إلى ما أصبح ضروريا فيما بعد، وهو معرفة المحقق واطلاعه على البيبليوغرافيات العربية لينظر إن كان قد تم تحقيق ما هو عازم على تحقيقه أم لا. ومع الإقبال الهائل على تحقيق التراث العربي ظهرت ضرورة ملحة لإنشاء مراكز متخصصة في الحفاظ على المخطوطات وفهرستها. ثم لم تلبث المكتبة العربية طويلا حتى صارت عامرة زاخرة بكتب فهارس المخطوطات. لم تخل تلك الفهارس من فوائد وتسهيلات على الباحثين، غير أنها ظلت دائما قاصرة عن الإلمام بجميع عناصر فهرسة المخطوطات نظرا لطابعها الورقي، وعدم وجود إمكانية يسيرة للتعديل والتحديت والمتابعة والتجديد.